Implementasi Sistem Informasi Manajemen Pendidikan dalam Meningkatkan Mutu Pendidikan di Madrasah - Suheri Suheri; Dian Hidayati (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This research explains how MI Al Muhtadin Plumbon uses an education management information system to improve the quality of education. The education management information system was created to meet the needs of madrasahs. Madrasas want computerized management of academic activities to improve service quality and to facilitate the teaching and learning process in madrasas. Methods of data collection, research using observation, interviews, and documentation. The results of the study show that MI Al Muhtadin Plumbon has implemented an education management information system through the use of various applications. Among them is the SIMPATIKA application (information system for educators and education staff of the ministry of religion), the internet-based learning application used at MI Al Muhtadin through YouTube Kids and Quizz media, as well as the new student admissions application (PPDB). At MI Al Muhtadin there are several elements that support and hinder the implementation of SIMDIK. The inhibiting element in the implementation of the education management information system is the lack of understanding of human resources related to technology, and what supports the implementation of the education management information system are the many parties who help and work together to overcome the limited human resources at MI Al Muhtadin Plumbon.